Dinamika Jaringan Aktor dalam Perizinan Dan Pengawasan PBG di Pekanbaru: Analisis Berdasarkan Pendekatan Teori Jaringan Kebijakan - Khairunsyah Purba; Syarifah Aini; Nurmaini Dalimunthe (Al-Manar Journal of Public Administration and Management, 2026)
The dynamics of actor networks in the permitting and supervision of Building Approval (PBG) in Pekanbaru require a comprehensive understanding, as they involve various parties with differing interests and authorities. This study employs the policy network theory approach to analyze the roles, functions, and interaction patterns among actors involved in the process of issuing permits and overseeing building construction. Identifying key actors, their reciprocal relationships, and the network structures formed within the context of local government policy implementation are essential aspects in assessing the effectiveness of urban development governance. The research findings indicate that interactions among government agencies such as the DPMPTSP, the Department of Public Works and Spatial Planning (PUPR), the Civil Service Police Unit (Satpol PP), business actors (consultants, developers), and civil society organizations play a strategic role in determining both the success and the challenges of PBG implementation. This study aims to provide an in-depth analysis of the policy network dynamics in decision-making related to PBG in Pekanbaru, and to offer recommendations for improving coordination, transparency, and the overall effectiveness of the policy moving forward.